New textbooks of science and their reference to the application of scientific method based on the aquatic resources. - Héctor Toledo Muñoz; Sara Zelada Muñoz; Carmen Soto Martínez (Universidad de Granada, 2012)
A new didactical curriculum model for teaching science based on aquatic resources has been applied to a group four hundred and fourteen students from primary education, just in establishments situated on the coastal edge of the Tenth Region of Los Lagos, Chile. The themes of the learning strategy were suggested activities in science texts, drawn from interdisciplinary workshops involving classroom teachers, aquatic resources, professional didactic teaching, marine ecology experts, geneticist, sea farmers, water resource management and scientists. The new texts were analyzed in comparison with textbooks commonly used by students of 7th and 8th grade of Basic Education, in Chile; in the lecture of "Study and Understanding of Nature". The test result showed a variety of procedural in the activities. It highlights the practical procedures, proposition of hypotheses, direct observation. We conclude that the textbooks of Natural Sciences - in the framework of a new teaching that integrates advances in scientific knowledge, technology and constructivism - are an innovative contribution to the meaningful, efficient and effective learning of science.